Malaria infections reinforce competitive asymmetry between two Ficedula flycatchers in a recent contact zone - Katarzyna Kulma; Matthew Low; Staffan Bensch; Anna Qvarnström (Molecular Ecology, 2013)
Parasites may influence the outcome of interspecific competition between closely related host species through lower parasite virulence in the host with which they share the longer evolutionary history. We tested this idea by comparing the prevalence of avian malaria ( H aemosporidia) lineages and their association with survival in pied and collared flycatchers ( F icedula hypoleuca and F . albicollis ) breeding in a recent contact zone on the S wedish island of Ö land. A nested PCR protocol amplifying haemosporidian fragments of mt DNA was used to screen the presence of malaria lineages in 1048 blood samples collected during 6 years. Competitively inferior pied flycatchers had a higher prevalence of blood parasites, including the lineages that were shared between the two flycatcher species. Multistate mark–recapture models revealed a lower survival of infected versus uninfected female pied flycatchers, while no such effects were detected in male pied flycatchers or in collared flycatchers of either sex. Our results show that a comparatively new host, the collared flycatcher, appears to be less susceptible to a local northern European malarial lineage where the collared flycatchers have recently expanded their distribution. Pied flycatchers experience strong reproductive interference from collared flycatchers, and the additional impact of species‐specific blood parasite effects adds to this competitive exclusion. These results support the idea that parasites can strongly influence the outcome of interspecific competition between closely related host species, but that the invading species need not necessarily be more susceptible to local parasites.